The Paradigm Shift of Maqāṣid al-Syarī’ah in Contemporary Society: From Protection to Development - Ilham Abdi Prawira; Rahmad Setyawan; Fahlul Ulum Ahmad Adnani (Academica: Journal of Multidisciplinary Studies, 2025)
Maqāṣid al-Syarī‘ah is the philosophical foundation of Islamic law that aims to realize welfare and prevent harm in human life. However, the classical formulation of maqāṣid al-Syarī’ah, which focuses on protecting the five basic needs (al-Dharūriyyāt al-Khams), faces serious challenges in responding to the complexities of contemporary society. Objective: This article aims to analyze the paradigm shift of maqāṣid al-Syarī’ah from a protection and preservation approach to a development and rights-based approach. Method: Using qualitative-descriptive methods through a literature review, this study examines the contributions of Ibn ‘Asyur and Jasser Auda’s thought in reconstructing the maqāṣid al-Syarī’ah as an adaptive and systemic framework for Islamic legal philosophy. Results: The results show that contemporary maqāṣid al-Syarī‘ah is no longer limited to individual interests but extends to universal values ​​such as social justice, human rights, religious freedom, and collective well-being. Conclusion: This article asserts that contextualizing the maqāṣid al-Syarī‘ah is a methodological necessity to maintain the relevance of Islamic law in addressing social, legal, and humanitarian challenges in the modern era.